Maternal Gene Expression Profiling During Pregnancy And Preeclampsia In Human Peripheral Blood Mononuclear Cells - Rajakumar, Augustine (2010)
Preeclampsia is a major obstetrical complication affecting maternal and fetal health. While it is clear that there is a substantial placental contribution to preeclampsia pathogenesis, the maternal contribution is less well characterized. We therefore performed a genome wide transcriptome analysis to explore disease-associated changes in maternal gene expression patterns in peripheral blood mononuclear cells (PBMCs). METHODS: Preeclampsia was defined as gestational hypertension, proteinuria and hyperurecimia. Total RNA was isolated from PBMCs obtained from women with uncomplicated pregnancies (n=5) and women with preeclamptic pregnancies (n=5). Gene expression analysis was carried out using Agilent oligonucleotide microarrays. Biological pathway analysis was undertaken using Ingenuity Pathway Analysis software. Quantitative real time PCR (QRTPCR) was performed to validate the gene expression changes of selected genes in normotensive and preeclamptic patients (n=12 each). RESULTS: We identified a total of 368 genes that were differentially expressed in women with preeclampsia compared to normal controls with false discovery rate (FDR) controlled at 10%. In follow up experiments we further analyzed the expression levels of a number of genes that were identified as altered by the microarray data including survivin (BIRC5), caveolin (CAV1), GATA binding protein-1 (GATA1), signal tranducer and activator of transcription 1 (STAT1), E2F transcription factor-1 (E2F1), fibronectin-1 (FN1), interleukin-4 (IL-4), matrix metalloprotease-9 (MMP-9) and WAP four-disulfide domain protein (WFDC-1) by QRTPCR. Additionally we performed immunoblot analysis and zymography to verify some of these candidate genes at the protein level. Computational analysis of gene function identified an anti-proliferative and altered immune function cellular phenotype in severe preeclamptic samples. CONCLUSIONS: We have characterized the genome-wide mRNA expression changes associated with preeclampsia-specific genes in circulating maternal blood cells at the time of delivery. In addition to providing information relating to the biological basis of the preeclampsia phenotype, our data provide a number of potential biomarkers for use in the further characterization of this disease.